2011
DOI: 10.1021/ie2006577
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Approach for Modeling Bubbles Rising in Non-Newtonian Fluids

Abstract: The present work reports a multiscale approach to describe the dynamics of a chain of bubbles rising in non-Newtonian fluids. By means of the particle image velocimetry (PIV) and the lattice Boltzmann (LB) simulation, a deep understanding of the complex flow pattern around a single bubble is gained at microscale. The interactions and coalescences between bubbles rising in non-Newtonian fluids are experimentally investigated by the PIV measurements, birefringence, and rheological characterization for both an is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The numerical difficulties that exist due to the complex physics of the free surface, coupled with the hyperbolic character of the constitutive equations used to describe the elastic properties of the material, did not allow the theoretical studies to proceed to the accurate reproduction of the experimentally observed 'velocity jump'. Additionally, no reported results exist for the stationary solutions, which could lie in the discontinuous region because the problem is approached using transient simulations only (Wagner, Giraud & Scott 2000;Malaga & Rallison 2007;Pillapakkam et al 2007;Frank et al 2012). There are still many open questions on the origin of the velocity jump.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical difficulties that exist due to the complex physics of the free surface, coupled with the hyperbolic character of the constitutive equations used to describe the elastic properties of the material, did not allow the theoretical studies to proceed to the accurate reproduction of the experimentally observed 'velocity jump'. Additionally, no reported results exist for the stationary solutions, which could lie in the discontinuous region because the problem is approached using transient simulations only (Wagner, Giraud & Scott 2000;Malaga & Rallison 2007;Pillapakkam et al 2007;Frank et al 2012). There are still many open questions on the origin of the velocity jump.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of parallel bubble coalescence and breakup could increase the predictability of gas–liquid equipment design as well as improve the understanding of the mechanisms of bubble coalescence and interaction systematically. The information about interactions and coalescence between parallel bubbles is also required for the multiscale modeling approach. , In this article, coalescence and breakup processes of multiple parallel bubbles in power-law fluid were studied systematically using VOF method, the critical bubble intervals for bubble coalescence were obtained for different bubble numbers and rheological properties, different regimes of multiple bubbles coalescence were classified according to dimensionless numbers, and the mechanisms of parallel bubble coalescence and breakup were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…They used this new approach to simulate a bubble rising in a viscoelastic fluid and were able to reproduce the experimentally observed cusp shape at the trailing end of the bubble. Frank et al [24] presented a multiscale approach to describe the dynamics of a chain of bubbles rising in non-Newtonian fluids using the particle image velocimetry (PIV) and the LBM simulations.…”
Section: Introductionmentioning
confidence: 99%